Effect of the use of passive body trunk exercise equipment on oxygen consumption and self‐efficacy for carrying out exercise in patients with type 2 diabetes. Issue 5 (23rd March 2020) - Kawae, Toshihiro; Iwaki, Daisuke; Nakashima, Yuki; Fudeyasu, Kenichi; Ishiguro, Tomoyasu; Kimura, Hiroaki; Sekikawa, Kiyokazu; Hamada, Hironobu; Ohno, Haruya; Yoneda, Masayasu
Abstract: Aims/Introduction: Considering the difficulty in inculcating the habit of exercise among patients with type 2 diabetes, devising an easily maintained means of exercise is preferable. Passive body trunk exercise equipment (PBTE) developed for home use might solve several problems related to exercise therapy, both for patients and clinical staff involved in diabetes treatment; however, its efficacy as a therapeutic exercise device for patients with diabetes has not been ascertained. The purpose of this study was to measure the exercise intensity and self‐efficacy of PBTE, and to determine whether PBTE is a useful tool for exercise therapy. Materials and Methods: The participants were 20 patients with type 2 diabetes, and the duration of exercise using the PBTE was set to 10 min. Oxygen consumption during exercise was measured, and self‐efficacy for continuing to exercise using the PBTE and for walking was evaluated after completion of the study. Results: The average exercise intensity using the PBTE was 1.7 metabolic equivalents, whereas the maximum exercise intensity was an average of 2.0 metabolic equivalents; the reported self‐efficacy for continuing to exercise using the PBTE was significantly higher than for walking. Conclusions: Exercise intensity using the PBTE is similar to low‐intensity walking, and thus, it might be a useful therapeutic exercise device for patients with type 2 diabetes. Furthermore, it could be an effective exercise device for diabetes patients who do not have regular exercise habits, especially with reduced motor function or lower leg muscle strength. Abstract : Given the low risk of falling when exercising in the seated position with passive body trunk exercise equipment, this approach could serve as a safe training exercise for patients with diabetes with musculoskeletal disabilities who do not exercise regularly.